2014
DOI: 10.4154/gc.2014.08
|View full text |Cite
|
Sign up to set email alerts
|

Late Coniacian- Early Campanian planktonic foraminiferal bioevents and biostratigraphy of the northern Tunisia

Abstract: Planktonic foraminifera were quantitatively analyzed across the Santonian succession and their boundaries at the Jebel Ennahli and Ettout sections, northern Tunisia. The continuous sedimentary succession is dominated by hemipelagic facies, allowing a good biostratigraphic correlation for this time interval. Fifty-fi fe planktonic foraminiferal species belonging to 13 genera have been identifi ed. The distribution pattern of 17 heterohelicids and 38 trochospiral forms reveals the identifi cation of 12 major bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…It is marked also by the extinction of both Muricohedbergella flandrini and Dicarinella asymetrica.Remarks: Some authors as[62,63] have equated the first appearance of Globotruncanita elevata with different levels of the Santonian Stage in North Africa and Mediterranean regions. Recent works show the base of the Campanian[64][65][66] and present work is marked by first appearance of Globotruncanita elevata taxon. In Egypt, many authors reported previously that Globotruncanita elevata is marked the base of the Campanian Stage in most localities[9,58,60,67,68,].…”
supporting
confidence: 50%
See 1 more Smart Citation
“…It is marked also by the extinction of both Muricohedbergella flandrini and Dicarinella asymetrica.Remarks: Some authors as[62,63] have equated the first appearance of Globotruncanita elevata with different levels of the Santonian Stage in North Africa and Mediterranean regions. Recent works show the base of the Campanian[64][65][66] and present work is marked by first appearance of Globotruncanita elevata taxon. In Egypt, many authors reported previously that Globotruncanita elevata is marked the base of the Campanian Stage in most localities[9,58,60,67,68,].…”
supporting
confidence: 50%
“…The first appearance of Globotruncanita elevata as indicated the marker of this boundary means prograding to oligotrophic episodes [85]. The lower Campanian shows the real diversity and radiation of globotruncanids, contusotruncanids and many foraminferal species in Northern Africa and Mediterranean regions [63,64], so at this boundary, many of mid Cretaceous planktonic foraminiferal taxa extincted globally [21,63]. The definition of Santonian/Campanian boundary is still mater of discussion [86][87][88].…”
Section: Santonian/campanian Boundary (Scbe)mentioning
confidence: 99%
“…Few high-resolution studies on general evolutionary trends, visible in the quantitative data from Campanian foraminifera communities exist. In general, most of quantitative studies on Late Cretaceous foraminiferal assemblages focus on developments around stage boundaries and/or events (e.g., Huber et al, 1999 ; Arz & Molina, 2001 ; Odin & Lamaurelle, 2001 ; Petrizzo, 2002a ; Caron et al, 2006 ; Elamri & Zaghbib-Turki, 2014 ; Elamri, Farouk & Zaghbib-Turki, 2014 ; Reolid et al, 2015 ). The vast majority deals with the Cretaceous- Paleogene turnover (e.g., Abramovich, Almogi-Labin & Benjamini, 1998 ; Li & Keller, 1998 ; Arenillas et al, 2000 ; Abramovich & Keller, 2002 ; Karoui-Yaakoub, Zaghbib-Turki & Keller, 2002 ; Premoli Silva, Emeis & Robertson, 2005 ; Gallala et al, 2009 ; Beiranvand & Ghasemi-Nejad, 2013 , see also Pardo & Keller, 2008 for a compilation of selected quantitative databases on the Cretaceous-Paaeogene boundary).…”
Section: Introductionmentioning
confidence: 99%